An overview of laparoscopic closure of duodenal perforation in a tertiary care centre - Kshetrimayum, Gobind; Sanjenbam, Shyamchand; Vumkhoching, Rosemary; Khumallambam, Ibomcha; Achom, Ranjita; Ingudam , Mahendra; Thokchom, Amataleima (International Journal of Research in Medical Sciences, 2023)
Duodenal ulcer perforation is one of the most commonly encountered condition in emergency surgery. Laparoscopic repair of the perforation has been reported in many cases since the first laparoscopic repair of a duodenal perforation in the year 1990 by Mouret et al. Aim and objectives were to study the clinical outcomes of laparoscopic repair of duodenal perforation in terms of duration of surgery, post operative pain, initiation of oral feeds, surgical site infection and duration of hospital stay. Over a 2 year period, 2018-2020, 20 patients with a presumptive diagnosis of perforated duodenal ulcers were considered for laparoscopic closure. Primary closure of the perforation was done with intracorporeal suturing followed by omental patch repair. The mean age was 38.75±8.53 years, mean duration of surgery was 97.80±7.89 minutes. The mean number of analgesic injection was 2.90±0.72. The mean duration of initiation of oral feeds was 3.20±0.41 days. The mean duration of removal of drain was 4.65±0.75 days and mean duration of hospital stay was 6.20±0.41 days. No intraoperative complications encountered. Postoperatively, none of the patients develop wound infections. In our setting, laparoscopic closure was found to be safe and a promising method in management of duodenal perforation as it appears to be more beneficial in terms of decreased post-operative pain, early initiation of oral feeds, decreased length of hospital stay and no major complications postoperatively. However, the procedure requires a surgeon with particular expertise in endoscopic suturing skills.